Purification of Peroxisomes in a Self-Generated Gradient - John Graham (The Scientific World Journal)
In iodixanol, peroxisomes are the densest organelle in the light mitochondrial fraction and are therefore easily separated from the other components (lysosomes, mitochondria, etc.) in a self-generated gradient. Self-generated gradients make sample handling very easy and are highly reproducible but need to be formed in either a vertical, near-vertical, or small volume high-performance fixed-angle rotor. The resolution of the peroxisomes is far superior than that in sucrose and, unlike in PercollⓇ there is no contamination from endoplasmic reticulum.